"A lot of people go insane behind that": coping with the trauma of being wrongfully convicted. Issue 3 (2nd July 2016) - DeShay, Rashaan A.
Abstract : Research has demonstrated that individuals may use different means to cope with traumatic life experiences. Using data collected during in-depth interviews with exonerees, this qualitative study explores the ways in which individuals that have been wrongfully convicted cope with that traumatic experience. The findings demonstrate that exonerees use both positive and negative coping techniques. Prayer and faith appear to be the most important coping mechanism used by this sample of exonerees. Additional coping mechanisms include meeting with other exonerees to discuss their experience, helping other exonerees, reflecting on their personal experience, and withdrawing from others. Policy implications are also discussed.